Characteristics of physical fitness level: A case study of new members male and female of the Pasopati student regiment - Ahmad Nasrulloh; Raden Yulchan Syafruddin; Rina Yuniana (MEDIKORA, 2022)
This study aimed to determine the characteristics of the physical fitness level of new members of the Pasopati student regiment. This study uses a survey method with test and measurement techniques. The population used were members of the Pasopati student regiment as many as 81 students. The sampling technique was carried out by purposive sampling so that a sample of 29 new members of the Pasopati student regiment was obtained. The instrument used in this study was the Indonesian Physical Fitness Test for adolescents aged 16-19 years. The data analysis technique used descriptive quantitative percentages. The results of the study show that the results of the research on the physical fitness of new members of the Pasopati Student regiment are known that the characteristics of physical fitness of new members of the Pasopati Student regiment can be described as (1) The physical fitness of new members of the male's Pasopati student regiment is included in the good category of 33.33%, (2 ) The level of physical fitness of new members of the female Pasopati student regiment is mostly in the good category as much as 60%, and (3) The physical fitness of all new members of the Pasopati Student regiment, both male and female, is included in the good category of 48.28%. Therefore, it is still very necessary to carry out intensive training to be able to improve physical fitness for new members of the Pasopati student regiment, especially speed, strength, and endurance exercises for the arm and shoulder muscles, and cardiorespiratory endurance because each member of the student regiment as the components of the state's defense and security reserves requires excellent physical fitness